IMPROVING ENGLISH LEARNING CULTURE THROUGH LEARNING MOTIVATION - Miftahul Jannah; Sahiruddin Sahiruddin (Studi Budaya Nusantara, 2020)
A learning culture is needed to facilitate the process of learning English for students and to increase student motivation in learning language (Kim, 2020). This research paper aim to examine and describe Indonesian EFL university students’ motivation whether integrative or instrumental in learning English as foreign language. The method used was quantitative by randomly asking the students  enrolled in undergraduate study program of English Literature in one of the Indonesian universities to fill out a questionnaire adapted from Attitude Motivation Test Battery (AMTB) that was developed by R.C. Gardner (1985). The questionnaire was administered to students who come from 2017 generations to 2020 generations. Moreover, this study also examine whether the differences existed in motivation between old students and new students. The data collected were analyzed by using SPSS program to find out the mean score and standard deviation as to answer the questions of this study. The results indicated that students’ motivation in learning English was more highly instrumental than integrative. This study also revealed that new students had more instrumental motivation and old students had more integrative motivation. Based on the findings, lecturers are expected to improve their way of learning for enhancement the students’ motivation. Learning culture developed should take into account and maintain the motivation of students in language learning.